Innovation in accessibility in astronomy: telescope automation and astronomical description with artificial intelligence - Oliveira, Aloisio de Souza; Alvim, Irllam; Vicente, Linda; Queiroz, Iago; Gonçalves, Gustavo de Queiroz; Terra, Daniel (Cadernos de Astronomia, 2025)
This project aims to democratize access to astronomy for people with visual impairments through the use of automation and artificial intelligence (AI). One of the main outcomes of the project was the development of the Space Allity application, designed from the beginning for this specific purpose. The system integrates telescope automation with the Space Allity app, created to make astronomy accessible to individuals with visual disabilities. The application captures images of celestial objects observed through the telescope and processes them using AI, which identifies the objects and generates detailed audio descriptions. Users can also explore an image gallery and customize settings to accommodate different visual impairment profiles. Additionally, an adapted box with Braille identification and an accessible assembly manual were created. The validation stage involved three participants with visual impairments from Guarapari-ES, Brazil, who actively contributed to the system’s evaluation and expressed enthusiasm about the audio descriptions and the team’s presentation. The results indicated a positive impact on inclusion and engagement with astronomy. However, improvements were identified in the durability of printed components and in the application interface. This study reinforces the role of technology in promoting scientific and social inclusion, transforming barriers into opportunities.
Keywords: astronomy; inclusion; visual impairment; artificial intelligence; Arduino